CANCER RISKS FROM DIAGNOSTIC RADIOLOGY - Ibrahim Nabeel Basri; Mohammed Mutlaq Alrashdi; Abdulhameed Ali Aloraini (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Diagnostic radiology plays a crucial role in healthcare by providing valuable insights into the diagnosis and management of various diseases. However, concerns have been raised regarding the potential risks of radiation exposure from these imaging techniques. This essay aims to explore the cancer risks associated with diagnostic radiology, focusing on the types of radiation, dose levels, and associated factors. The methodology involves a comprehensive review of relevant literature from reputed journals, highlighting the existing evidence on radiation-induced cancer and the necessity of implementing appropriate protocols to minimize risks. The results demonstrate a complex relationship between radiation exposure and cancer development, with varying degrees of risk depending on factors such as age, gender, dose, and frequency of imaging. The discussion further delves into the importance of patient education, informed consent, and the adoption of dose optimization strategies to mitigate these risks. In conclusion, while diagnostic radiology undoubtedly offers significant clinical benefits, it is crucial to strike a balance between obtaining accurate diagnostic information and minimizing potential harm to patients.